Hukum Transplantasi Katup Babi Pada Manusia dalam Sudut Pandang Islam - Zulfa Sukarno; Fahma Nabila; Cleo Rafhael Putri Rahmanata (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
This study examines the legality of pig valve transplantation in humans from an Islamic perspective, with the aim of understanding the differences of opinion that exist among scholars and medical professionals. This literature review identified two main views: first, arguments in favor of the use of pig valves in emergency situations, which adhere to the principle that patient safety should be the top priority. Proponents of this view argue that in critical conditions, such as heart failure, the use of pig valves can be justified to save lives, given the limited halal alternatives available. Second, there is a view that rejects the use of pig valves, arguing that the laws of halal and haram in Islam cannot be ignored, even in a medical context. Opponents argue that more sharia-compliant solutions should be sought, such as the use of valves made from synthetic materials or halal animals. This study shows that the legal issue of pig valve transplantation is multidimensional, encompassing medical, ethical, and religious aspects. Therefore, a constructive dialogue is needed between scholars, medical practitioners, and the community to find a solution that is acceptable to all parties, while respecting Islamic principles in medical decision-making.